Diagnosis and control of diseases of fish and shellfish - Austin, B. (Brian), 1951-; Newaj-Fyzul, Aweeda, 1964- (Hoboken, NJ : Wiley, 2017)
There has been a continual expansion in aquaculture, such that total production is fast approaching that of wild-caught fisheries. Yet the expansion is marred by continued problems of disease. New pathogens emerge, and others become associated with new conditions. Some of these pathogens become well established, and develop into major killers of aquatic species. Diagnosis and Control of Diseases of Fish and Shellfish focuses on the diagnosis and control of diseases of fish and shellfish, notably those affecting aquaculture. Divided into 12 chapters, the book discusses the range of bacterial, viral and parasitic pathogens, their trends, emerging problems, and the relative significance to aquaculture. Developments in diagnostics and disease management, including the widespread use of serological and molecular methods, are presented. Application/dose and mode of action of prebiotics, probiotics and medicinal plant products used to control disease are examined, as well as the management and hygiene precautions that can be taken to prevent/control the spread of disease. This book will be a valuable resource for researchers, students, diagnosticians, veterinarians, fish pathologists and microbiologists concerned with the management of diseases of fish and shellfish.
Bacterial diagnosis and control in fish & shellfish / Dr. Mags Crumlish -- Complexities of diagnostics of viruses affecting farmed aquatic species / Manfred Weidmann -- Parasitic diseases in aquaculture : their biology, diagnosis and control / Giuseppe Paladini, Matt Longshaw, Andrea Gustinelli and Andrew P. Shinn -- Modern methods of diagnosis / Ahran Kim, Thanh Luan Nguyen, Do-Hyung Kim -- Immunostimulant diets and oral vaccination in fish / Eva Vallejos-Vidal, Felipe Reyes-Lopez and Simon MacKenzie -- Prebiotics and synbiotics / Seyed Hossein Hoseinifar, Yun-Zhang Sun , Zhigzhang Zhou -- Probiotics for disease control in aquaculture / S.M. Sharifuzzaman and B. Austin -- Use of medicinal plants in aquaculture / Reverter M., Bontemps N., Sasal P., Saulnier, D. -- Antibiotics and disinfectants / Brian Austin -- Management techniques and disease control / Aweeda Newaj-Fyzul and Brian Austin.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Fishes -- Diseases; Shellfish -- Diseases; Aquaculture; TECHNOLOGY & ENGINEERING / Agriculture / General; Fish Diseases -- diagnosis; Shellfish; Bacteriological Techniques -- veterinary; Aquaculture; Electronic books